Effect of the injection moulding processing conditions on the development of pea protein‐based bioplastics. Issue 20 (5th February 2016) - Perez-Puyana, V.; Felix, M.; Romero, A.; Guerrero, A.
ABSTRACT: Bioplastic materials from renewable polymers, like proteins, constitute a highly interesting field for important industrial applications such as packaging, agriculture, etc., in which thermo‐mechanical techniques are increasingly being used. Pea protein‐based bioplastics can be made through a mixing process followed by an injection moulding. The objective of this study was to investigate the influence of different injection parameters (moulding time and injection pressure) on the properties exhibited by the final bioplastics obtained. A dynamic mechanical analysis and tensile strength measurements were performed, along with water absorption capacity and transparency tests. The results indicated that the major differences between bioplastics obtained at different moulding times are in transparency and in the Young's Moduli, exhibiting lower values as moulding time increases. On the other hand, modifying the injection pressure lead to more consistent bioplastics which differed mainly in the elastic component ( E ′ profiles) and in the strain at break. Furthermore, the water uptake was more than 100% in almost all the different bioplastics processed because of its hydrophilic character, so they could be considered as potential sources for absorbent material. © 2016 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2016, 133, 43306. Abstract :